TRIAD XII: Are Patients Aware of and Agree With DNR or POLST Orders in Their Medical Records. Issue 3 (September 2019) - Mirarchi, Ferdinando L.; Juhasz, Kristin; Cooney, Timothy E.; Puller, Justin; Kordes, Tammy; Weissert, Lynn; Lewis, Mary Lynn; Intrieri, Brandon; Cook, Nathan
Abstract : Objective: The aim of the study was to determine (1) whether do-not-resuscitate (DNR) orders created upon hospital admission or Physician Orders for Life-Sustaining Treatment (POLST) are consistent patient preferences for treatment and (2) patient/health care agent (HCA) awareness and agreement of these orders. Methods: We identified patients with DNR and/or POLST orders after hospital admission from September 1, 2017, to September 30, 2018, documented demographics, relevant medical information, evaluated frailty, and interviewed the patient and when indicated the HCA. Results: Of 114 eligible cases, 101 met inclusion criteria. Patients on average were 76 years old, 55% were female, and most white (85%). Physicians (85%) commonly created the orders. A living will was present in the record for 22% of cases and a POLST in 8%. The median frailty score of "4" (interquartile range = 2.5) suggested patients who require minimal assistance. Thirty percent of patients requested cardiopulmonary resuscitation and 63% wanted a trial attempt of aggressive treatment if in improvement is deemed likely. In 25% of the cases, patients/HCAs were unaware of the DNR order, 50% were unsure of their prognosis, and another 40% felt their condition was not terminal. Overall, 44% of the time, the existing DNR, and POLST were discordant with patient wishes and 38% were rescinded. Of the 6% not rescinded, further clarifications were required. Discordant orders were associated with younger, slightly less-frail patients. Conclusions: Do-not-resuscitate and POLST orders can often be inaccurate, undisclosed, and discordant with patient wishes for medical care. Patient safety and quality initiatives should be adopted to prevent medical errors.